Myasthenia gravis with Castleman disease: A case report with review of literature - Sujit Nandy; Debashis Bhattacharya; Somenath Kundu; Uttara Chatterjee (Indian Journal of Pathology and Microbiology)
Myasthenia gravis is an autoimmune disorder caused by the formation of autoantibodies directed against the synapses of neuromuscular junction. It is most commonly associated with other non-thymomatous lesions. Castleman disease is one of them, which is a benign lymphoproliferative disorder of uncertain origin. Only eight cases of myasthenia gravis associated with Castleman disease have been described so far. Here, we take the opportunity to describe a case of myasthenia gravis with Castleman disease simulating thymoma clinically and radiologically along with review of literature of this rare association. Patient developed myasthenic crisis in the immediate post-operative period which is more common in myasthenia gravis with Castleman disease rather than myasthenia gravis with thymoma.